Seroprevalence of Herpes Simplex Virus Type 1 and 2 in Taiwan and Risk Factor Analysis, 2007 - Shen, Jen-Hsiang (PLoS One, 2015)
BACKGROUND: Herpes simplex virus type 1 (HSV-1) and 2 (HSV-2) are common human pathogens and might cause severe illness. Following primary infection, the viruses establish lifelong latent infection and are transmitted by close contact, both sexual and nonsexual. However, the information about the seroprevalence of HSV-1 and HSV-2 across all age groups is limited. METHODS: Residual sera collected during the nationwide serosurvey in 2007 in Taiwan were selected for the study. The enzyme-linked immunosorbent assay was used to detect anti-HSV-1 and anti-HSV-2 type-specific glycoprotein IgG. Demographics and personal health data were used for risk analysis. RESULTS: A total of 1411 and 1072 serum samples were included for anti-HSV-1 and anti-HSV-2 seroprevalence analysis, respectively. The weighted overall seroprevalence was 63.2% for HSV-1, and 7.7% for HSV-2, respectively. The HSV-1 seropositive rate was 19.2% for those less than 5 years old, increased to 46.4% for those aged 5–13 years, 60.9% for those aged 14–29 years, and reached as much as 95.0% for those aged over 30 years. In contrast, the HSV-2 seropositve rate was 1.6% for those less than 30 years old, rose to 10.1% for those age 30–39 years, and was up to 31.2% for those aged over 60 years. A significantly higher HSV-2 seropositive rate was noted in females than males aged over 40 years (26.3% v.s. 16.8%), and the overall HSV-2 seropositive rate was almost twice higher in females than males. Smoking history, drinking habit, and educational level were associated with the HSV-1 seropositivity. Female gender and rural residence were independent factors for the HSV-2 seropositivity. CONCLUSIONS: An obvious increase of primary HSV-1 infection occurred in late adolescents and young adults, joined by the rise of HSV-2 infection in middle-aged adults, especially females. The acquistion and transmission of HSV warrant further studies in the susceptible population.